Multivariate analysis of some important quantitative traits in rapeseed (Brassica napus) advanced lines - V Rameeh (Journal of Oilseed Brassica, 2026)
Development of new rapeseed (Brassica napus L.) cultivars requires efficient tools to monitor traitsrelationship in a breeding program. Twenty four rapeseed genotypes including 2 cultivars and 22 advancedlines were evaluated based on randomized complete block design with three replications. Significantgenotypes effects were exhibited for phenological traits, plant height, yield components and seed yield,indicating significant genetic differences among the genotypes. High broad sense heritability were estimatedfor phenological traits, pods on main axis and seed yield signifying selection gain for improving these traits willbe high. Duration of flowering and pods on main axis had high value of genetic coefficient of variation. Theresults of factor analysis exhibited four factors including sink factor (pod per plant, pods length and seedyield), fixed capital factor (phenological traits), secondary fixed capital factor (duration of flowering) andmetric factor (plant height). The results of stepwise regression analysis revealed that plant height and podsper plant had more decreasing and increasing effects on seed yield, respectively. On the basis of clusteranalysis, the genotypes were classified in four groups and the group with high seed yield had high mean valueof pods per plant.